Approximation of limit amplitude diagram for destructive elements of safety devices - Artiukh Viktor; Mazur Vladlen; Sahirov Yurii; Geraskin Yuri (E3S Web of Conferences, 2020)
The maximum stress of the cycle should be limited not by yield strength but by tensile strength of detail material intended to be destructed. Therefore, such widespread linear approximations of Haigh diagram and conditions of Soderberg and Serensen-Kinasoshvili are not applicable for such details. Safety factor of fatigue strength of safety devices destructive elements should not exceed 1.0. Therefore, it is undesirable to use modified condition of Goodman for destructive elements. Two new variants of linear approximation of Haigh limit amplitudes diagram were developed. Both variants have proven their efficiency in design and operation of safety devices with destructive elements in framework of laboratory ‘Protection of metallurgical machines from breakdowns’ of the Chief mechanic department of PJSC ‘ILYICH IRON AND STEEL WORKS’ (Mariupol city, Ukraine).